Prognostic Value of the Modified Glasgow Prognostic Score in Patients with Metastatic Renal Cell Carcinoma Receiving Nivolumab as Second-Line Therapy: A Multicentre Retrospective Cohort Study - Sedat Biter; Ertuğrul Bayram; Tolga Köşeci; Mehmet Cihan İçli; Ahmet Melih Arslan; Faruk Recep Özalp; Nadiye Sever; Ahmet Ünsal; Nargiz Majidova Altuntaş; Mustafa Seyyar; Gülhan Dinç; Mahmut Büyükşimşek; et al. (Medicina, 2026)
Background and Objectives: The modified Glasgow Prognostic Score (mGPS)—a composite of serum C-reactive protein (CRP) and albumin—simultaneously reflects systemic inflammatory activity and nutritional reserve. Its specific prognostic role in patients with metastatic renal cell carcinoma (mRCC) treated with nivolumab in the second-line setting has not previously been examined in a large multicentre cohort. The aims of this study are to determine whether baseline mGPS independently predicts overall survival (OS) and progression-free survival (PFS) in this population and whether its discriminatory capacity compares favourably with the International Metastatic RCC Database Consortium (IMDC) risk score. Methods: This multicentre retrospective cohort study included 174 consecutive patients with histopathologically confirmed mRCC who progressed on first-line VEGF-targeted tyrosine kinase inhibitor (TKI) therapy and subsequently received nivolumab monotherapy at six oncology centres in Türkiye between January 2015 and December 2023. Baseline mGPS was calculated from serum albumin and CRP measured within four weeks before treatment initiation. Kaplan–Meier analysis with log-rank testing and Cox proportional-hazards regression were used for survival analyses; discriminatory capacity was quantified using Uno’s concordance (C) statistic. Results: The median follow-up was 24.2 months. The median OS was 44.5, 15.3, and 10.0 months for the mGPS 0, 1, and 2 groups, respectively (log-rank p < 0.0001); the median PFS was 6.7, 4.2, and 2.6 months (p = 0.022). On multivariable analysis, mGPS 2 independently predicted inferior OS (hazard ratio [HR] 3.61, 95% confidence interval [CI] 1.78–7.31; p < 0.001) and PFS (HR 1.87, 95% CI 1.17–2.97; p = 0.008). Uno’s C-statistic for OS was numerically higher for the combined mGPS + IMDC model (0.70) than for either the mGPS (0.66) or IMDC (0.63) alone; these differences were not formally tested and are presented descriptively. Conclusions: Baseline mGPS is a simple, inexpensive, and independent prognostic biomarker in mRCC patients treated with second-line nivolumab, providing discriminatory information that may be complementary alongside IMDC risk stratification. Prospective validation in randomised trials is warranted.